A battery separator and a method for preparing the same

By setting a ceramic layer and a glue coating layer on the base layer of the battery separator and adjusting its surface roughness, the existing battery separator has solved the problem of high roughness and low coverage, and a high coverage and low roughness separator is achieved, which improves the bonding strength and stability of the battery.

CN119786887APending Publication Date: 2025-04-08SINOMA LITHIUM BATTERY SEPARATOR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993308.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing battery separators have problems such as high roughness and low glue coating coverage, which affects the stability and adhesion of the battery separators.

Method used

By providing a ceramic layer and a glue coating layer on the base layer and adjusting the surface roughness of the ceramic layer and the glue coating layer, the roughness of the ceramic layer is lower than that of the glue coating layer, thereby improving the coverage of the glue coating layer.

Benefits of technology

A low roughness and high coverage battery separator is achieved, which improves bonding strength and reduces powder loss, and meets the stability and bonding requirements during battery production and assembly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786887A_ABST
    Figure CN119786887A_ABST
Patent Text Reader

Abstract

The present application provides a battery separator and a preparation method thereof, wherein the battery separator comprises a substrate layer, a ceramic layer arranged on at least one surface of the substrate layer, and a glue layer arranged on the surface of the ceramic layer; the ceramic layer comprises ceramic particles, and the glue layer comprises a binder; the surface roughness of the ceramic layer is 100nm to 300nm; the surface roughness of the glue layer is 200nm to 400nm; the surface roughness of the ceramic layer is less than the surface roughness of the glue layer; the coverage of the glue layer is 85% to 100%, and the coverage of the ceramic layer is 95% to 100%. The battery separator of the present application has high coverage, low roughness, high bonding strength and low powder loss, and can enable stable production during the battery assembly process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery separators, and in particular to a battery separator and a preparation method thereof. Background Art

[0002] In the field of battery separator manufacturing technology, separator coating is an important technology that can improve the safety and performance of the battery. Forming a coating on the surface of the separator base film can improve the performance of the separator, such as thermal stability, mechanical strength, puncture resistance and adhesion. At present, the thermal stability, mechanical strength and puncture resistance of the separator are mainly improved by coating a ceramic layer; and then the adhesion of the separator is improved by coating a rubber layer on the surface of the ceramic layer to reduce the internal resistance of the separator and increase the energy density of the battery. However, due to the high surface roughness of the ceramic layer, the rubber layer has a high roughness and low coverage, which affects the usability of the battery separator.

[0003] The battery separators in the prior art still have high roughness and low glue coverage, and cannot meet the stability and adhesion requirements during the battery production and assembly process. Summary of the invention

[0004] The purpose of this application is to provide a battery separator with high coverage and low roughness to meet the stability and adhesion requirements of the battery separator during battery production and assembly, and also to provide a method for preparing the battery separator. The specific technical solution is as follows:

[0005] The first aspect of the present application provides a battery separator, which includes a substrate layer, a ceramic layer arranged on at least one surface of the substrate layer, and a glue layer arranged on the surface of the ceramic layer; the ceramic layer includes ceramic particles, and the glue layer includes a binder; the surface roughness of the ceramic layer is 100nm~300nm; the surface roughness of the glue layer is 200nm~400nm; the surface roughness of the ceramic layer is less than the surface roughness of the glue layer; the coverage of the glue layer is 85%~100%, and the coverage of the ceramic layer is 95%~100%.

[0006] In some embodiments of the present application, the thickness of the ceramic layer is 0.95 μm to 1.75 μm, and the surface density is 1.35 g / m 2 ~3.4g / m 2 , the bulk density is 0.77g / (m 2 ·μm)~2.72g / (m 2 ·μm).

[0007] In some embodiments of the present application, the thickness of the coating layer is 0.5 μm to 1.5 μm, and the surface density is 0.5 g / m 2 ~1.6g / m 2, the bulk density is 0.4g / (m 2 ·μm)~1.8g / (m 2 ·μm).

[0008] In some embodiments of the present application, the thickness of the ceramic layer is 1.1 μm to 1.5 μm, and the surface density is 2.2 g / m 2 ~2.8g / m 2 , the bulk density is 1.47g / (m 2 ·μm)~2.55g / (m 2 ·μm).

[0009] In some embodiments of the present application, the thickness of the adhesive layer is 0.9 μm to 1.3 μm, and the surface density is 0.65 g / m 2 ~0.9g / m 2 , the bulk density is 0.5g / (m 2 ·μm)~1.0g / (m 2 ·μm).

[0010] In some embodiments of the present application, the ceramic particles are selected from at least one of silica, alumina, magnesium oxide, zirconium oxide, titanium oxide, calcium oxide, boehmite, aluminum nitride, boron nitride, barium sulfate, calcium fluoride, and barium fluoride; and the particle size of the ceramic particles is 500nm to 800nm.

[0011] In some embodiments of the present application, the binder is selected from at least one of polyvinylidene fluoride homopolymer, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-methyl methacrylate copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-acrylic acid copolymer, polymethyl methacrylate, polyethylene, and acrylate polymer; the primary particle size of the binder is 80nm to 300nm.

[0012] The second aspect of the present application provides a method for preparing the battery separator provided in the first aspect of the present application, which comprises the following steps:

[0013] (1) preparing a ceramic slurry: dispersing the ceramic particles in water, grinding at 300 rpm to 800 rpm for 0 to 4 times, with a grinding flow rate of 10 L / min to 30 L / min, and then filtering to obtain a ceramic slurry;

[0014] (2) preparing a coating slurry: dispersing the binder in water, grinding 1 to 6 times at 100 rpm to 500 rpm, with a grinding flow rate of 10 L / min to 30 L / min, homogenizing and filtering to obtain a coating slurry, wherein the homogenization pressure is 200 bar to 600 bar, the number of homogenizations is 1 to 6 times, and the homogenization flow rate is 1 L / min to 20 L / min;

[0015] (3) Ceramic layer coating: transferring the ceramic slurry to a gravure roller, the substrate layer being in contact with the gravure roller, transferring the ceramic slurry to at least one surface of the substrate layer, and drying at 50° C. to 80° C. to obtain an intermediate film; the intermediate film includes the substrate layer and the ceramic layer;

[0016] (4) Glue coating: The glue slurry is transferred to a gravure roller, the intermediate film is in contact with the gravure roller, the glue slurry is transferred to the surface of the ceramic layer, and dried at 50° C. to 80° C. to obtain the battery separator.

[0017] In some embodiments of the present application, the solid content of the ceramic slurry is 20% to 50%, and the solid content of the glue coating slurry is 5% to 20%.

[0018] In some embodiments of the present application, in the ceramic slurry, the particle size of the ceramic particles satisfies: D10 ≥ 0.1 μm, 0.2 μm ≤ D50 ≤ 0.8 μm, D90 ≤ 2 μm, and in the coating slurry, the particle size of the binder satisfies: D10 ≤ 1 μm, 1 μm < D50 ≤ 3 μm, D90 ≤ 6 μm.

[0019] Beneficial effects of this application:

[0020] The present application provides a battery separator and a preparation method thereof, wherein the battery separator is composed of a substrate layer, a ceramic layer disposed on at least one surface of the substrate layer, and a glue layer disposed on the surface of the ceramic layer. By reducing the roughness of the ceramic layer and the glue layer, and making the roughness of the ceramic layer lower than the roughness of the glue layer, the coverage of the glue layer is increased, and a battery separator with low roughness and high coverage is obtained. The battery separator has high bonding strength and low powder loss, and can enable stable production during the battery assembly process.

[0021] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0023] Figure 1 A schematic diagram of a battery separator according to an embodiment of the present application;

[0024] In the figure, 10. battery separator, 11. substrate layer, 12. ceramic layer, 13. adhesive layer. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0026] The first aspect of the present application provides a battery separator, such as Figure 1 The battery separator 10 includes a substrate layer 11, a ceramic layer 12 arranged on at least one surface of the substrate layer, and a rubber layer 13 arranged on the surface of the ceramic layer; the ceramic layer 12 includes ceramic particles, and the rubber layer 13 includes a binder; the roughness of the ceramic layer 12 is 100nm~300nm; the roughness of the rubber layer 13 is 200nm~400nm; the surface roughness of the ceramic layer is less than the surface roughness of the rubber layer; the coverage of the rubber layer 13 is 85%~100%, and the coverage of the ceramic layer is 95%~100%. For example, the roughness of the ceramic layer 12 can be 100nm, 130nm, 155nm, 180nm, 200nm or a range consisting of any two of the values ​​therein; the roughness of the rubber layer 13 can be 200nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm or a range consisting of any two of the values ​​therein; the coverage of the rubber layer 13 can be 85%, 88%, 90%, 93%, 95%, 98%, 100% or a range consisting of any two of the values ​​therein; the coverage of the ceramic layer 12 can be 95%, 96%, 98%, 99%, 100% or a range consisting of any two of the values ​​therein.

[0027] The inventors found that a ceramic layer with a low surface roughness is not only conducive to the uniform coating of the ceramic slurry and improves the coverage of the ceramic layer, but also conducive to the subsequent coating of the adhesive layer, so as to obtain a battery separator with low roughness and high coverage. By adjusting the surface roughness of the ceramic layer within the above range, the coverage of the ceramic layer can reach more than 95%, so that the coating of the adhesive layer slurry can be more uniform, and the coverage of the adhesive layer is improved. Furthermore, the surface roughness of the adhesive layer is greater than the surface roughness of the ceramic layer, but the smaller the surface roughness of the adhesive layer, the more uniform the coating and the higher the coverage. By adjusting the surface roughness of the adhesive layer within the above range, the coverage of the adhesive layer is further improved, and the coverage of the adhesive layer reaches 85% to 100%.

[0028] In general, the surface roughness of the ceramic layer is lower than that of the adhesive layer, which can make the adhesive layer slurry more evenly coated and increase the coverage of the adhesive layer to more than 85%. The smaller the surface roughness of the adhesive layer, the more evenly coated and the higher the coverage; the greater the surface roughness of the ceramic layer, the more difficult it is to coat evenly and the lower the coverage.

[0029] The present application improves the coverage of the ceramic layer and the rubber coating layer by regulating the surface roughness of the ceramic layer and the rubber coating layer, so that the battery separator has higher bonding strength and lower powder loss, which can meet the stability and bonding requirements of the battery separator during the battery production and assembly process.

[0030] In the present application, the substrate layer includes two opposite first surfaces and a second surface in the thickness direction, and the ceramic layer is coated on at least one surface of the substrate layer. Those skilled in the art should understand that the ceramic layer can be coated on the first surface, or on the second surface, or on the first surface and the second surface at the same time. Those skilled in the art can make a selection based on actual needs.

[0031] In the present application, there is no particular limitation on the type of the substrate layer, as long as the purpose of the present application can be achieved. For example, the substrate layer may include but is not limited to at least one of polyethylene and polypropylene.

[0032] In some embodiments of the present application, the thickness of the ceramic layer is 0.95 μm to 1.75 μm, and the surface density is 1.35 g / m 2 ~3.4g / m 2 , the bulk density is 0.77g / (m 2 ·μm)~2.72g / (m 2 Preferably, the thickness of the ceramic layer is 1.1 μm to 1.5 μm, and the surface density is 2.2 g / m 2 ~2.8g / m 2 , the bulk density is 1.47g / (m 2 ·μm)~2.55g / (m 2 ·μm). For example, the thickness of the ceramic layer can be 0.95μm, 1.0μm, 1.1μm, 1.15μm, 1.25μm, 1.33μm, 1.4μm, 1.5μm, 1.52μm, 1.6μm, 1.68μm, 1.75μm or a range consisting of any two of these values; the surface density of the ceramic layer can be 1.35g / m 2 , 1.6g / m 2 , 1.75g / m 2 , 1.9g / m 2 , 2.1g / m 2 , 2.2g / m 2 , 2.5g / m 2 , 2.75g / m 2 , 2.8g / m 2 3.2g / m 2 3.4g / m 2Or a range consisting of any two values; the bulk density of the ceramic layer can be 0.77g / (m 2 ·μm)、0.8g / (m 2 ·μm)、1.0g / (m 2 ·μm)、1.23g / (m 2 ·μm)、1.44g / (m 2 ·μm)、1.65g / (m 2 ·μm)、1.9g / (m 2 ·μm)、2.07g / (m 2 ·μm)、2.34g / (m 2 ·μm)、2.59g / (m 2 ·μm)、2.72g / (m 2 ·μm) or a range consisting of any two of the values. By adjusting the thickness and surface density of the ceramic layer within the above range, a ceramic layer with a bulk density within the above range can be prepared, and a ceramic layer with low surface roughness and high coverage can be further obtained, which is beneficial to improving the peeling strength of the ceramic layer, and at the same time, the air permeability of the ceramic layer can be guaranteed.

[0033] In some embodiments of the present application, the thickness of the coating layer is 0.5 μm to 1.5 μm, and the surface density is 0.5 g / m 2 ~1.6g / m 2 , the bulk density is 0.4g / (m 2 ·μm)~1.8g / (m 2 Preferably, the thickness of the coating layer is 0.9 μm to 1.3 μm, and the surface density is 0.65 g / m 2 ~0.9g / m 2 , the bulk density is 0.5g / (m 2 ·μm)~1.0g / (m 2 ·μm). For example, the thickness of the rubber coating layer can be 0.5μm, 0.7μm, 0.9μm, 1.05μm, 1.3μm, 1.5μm or a range consisting of any two of these values; the surface density of the rubber coating layer can be 0.5g / m 2 , 0.6g / m 2 , 0.65g / m 2 , 0.73g / m 2 , 0.8g / m 2 , 0.85g / m 2 , 0.9g / m 2 , 1.1g / m 2 , 1.2g / m 2 1.35g / m 2 , 1.44g / m 2, 1.6g / m 2 Or a range consisting of any two values; the bulk density of the coating layer can be 0.4g / (m 2 ·μm)、0.5g / (m 2 ·μm)、0.8g / (m 2 ·μm)、0.94g / (m 2 ·μm)、1.0g / (m 2 ·μm)、1.2g / (m 2 ·μm)、1.38g / (m 2 ·μm)、1.66g / (m 2 ·μm)、1.8g / (m 2 ·μm) or a range consisting of any two of the values. By adjusting the thickness and surface density of the coating layer within the above range, a coating layer with a bulk density within the above range can be prepared, and a coating layer with low surface roughness and high coverage can be further obtained, which is beneficial to improving the adhesion of the battery separator, and the air permeability of the coating layer can be guaranteed.

[0034] In some embodiments of the present application, the ceramic particles are selected from at least one of silicon dioxide, aluminum oxide, magnesium oxide, zirconium oxide, titanium oxide, calcium oxide, boehmite, aluminum nitride, boron nitride, barium sulfate, calcium fluoride, and barium fluoride; the particle size of the ceramic particles is 500nm to 800nm. For example, the particle size of the ceramic particles can be 500nm, 550nm, 580nm, 620nm, 680nm, 710nm, 750nm, 800nm, or a range consisting of any two of the values. By selecting the above-mentioned types of ceramic particles and controlling the particle size of the ceramic particles within the above-mentioned range, a ceramic layer with low roughness and high coverage can be prepared, providing conditions for uniform coating of the rubber layer.

[0035] In some embodiments of the present application, the binder is selected from at least one of polyvinylidene fluoride homopolymer, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-methyl methacrylate copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-acrylic acid copolymer, polymethyl methacrylate, polyethylene, and acrylate polymers. For example, polyvinylidene fluoride includes but is not limited to polyvinylidene fluoride. The primary particle size of the binder is 80nm to 300nm. For example, the primary particle size of the binder can be 80nm, 120nm, 150nm, 175nm, 200nm, 228nm, 260nm, 300nm or a range consisting of any two of the values. By selecting the above-mentioned types of binders and controlling the particle size of the binder within the above-mentioned range, a low roughness, high coverage glue layer can be prepared, the bonding strength of the battery separator is improved, and the amount of powder loss of the battery separator is reduced.

[0036] In the present application, the substrate layer, ceramic particles, binder, etc. are all conventional materials available on the market, and the present application has no particular restrictions on their sources, as long as the purpose of the present application can be achieved.

[0037] The second aspect of the present application provides a method for preparing the battery separator provided in the first aspect of the present application, which comprises the following steps:

[0038] (1) Preparing ceramic slurry: dispersing ceramic particles in water, grinding at 300 rpm to 800 rpm for 0 to 4 times, with a grinding flow rate of 10 L / min to 30 L / min, and then filtering to obtain ceramic slurry. In some embodiments of the present application, in the ceramic slurry, the particle size of the ceramic particles satisfies: D10 ≥ 0.1 μm, 0.2 μm ≤ D50 ≤ 0.8 μm, and D90 ≤ 2 μm.

[0039] (2) Preparing a coating slurry: Disperse the binder in water, grind 1 to 6 times at 100 rpm to 500 rpm, the grinding flow rate is 10 L / min to 30 L / min, and filter to obtain a coating slurry after homogenization. The homogenization pressure is 200 bar to 600 bar, the homogenization times are 1 to 6 times, and the homogenization flow rate is 1 L / min to 20 L / min. In some embodiments of the present application, in the coating slurry, the particle size of the binder satisfies: D10 ≤ 1 μm, 1 μm < D50 ≤ 3 μm, and D90 ≤ 6 μm.

[0040] (3) Ceramic layer coating: transferring the ceramic slurry to a gravure roller, the substrate layer is in contact with the gravure roller, transferring the ceramic slurry to at least one surface of the substrate layer, and drying at 50° C. to 80° C. to obtain an intermediate film; the intermediate film includes the substrate layer and the ceramic layer;

[0041] (4) Glue coating: The glue slurry is transferred to the gravure roller, the intermediate film is in contact with the gravure roller, the glue slurry is transferred to the surface of the ceramic layer, and dried at 50°C to 80°C to obtain a battery separator.

[0042] In step (1), by controlling the grinding speed, grinding times and grinding flow rate within the above range and filtering, the particle size of the ceramic particles in the ceramic slurry can be reduced so that the particle size is controlled within the above range, thereby increasing the packing density of the ceramic layer and reducing the surface roughness of the ceramic layer.

[0043] In step (2), by controlling the grinding speed, grinding times and grinding flow rate within the above range, and through homogenization and filtration treatment, the particle size of the binder in the coating slurry can be reduced so that its particle size is controlled within the above range, thereby increasing the packing density of the coating layer and reducing the surface roughness of the coating layer.

[0044] In step (1) and step (2), the present application has no particular limitation on the grinding method, as long as the purpose of the present application can be achieved. For example, the grinding can be carried out by a Langling NT-V30L horizontal sand mill.

[0045] In step (1) and step (2), the present application has no particular restrictions on the filtering method, as long as the purpose of the present application can be achieved. For example, a high-mesh filter can be used to filter particles with larger particle sizes. The present application has no particular restrictions on the mesh number of the filter, as long as the purpose of the present application can be achieved.

[0046] In step (2), the present application has no particular limitation on the homogenization method, as long as the purpose of the present application can be achieved. For example, an Antos AH-PILOT 22 homogenizer can be used for homogenization.

[0047] In step (3) and step (4), there is no particular limitation on the drying method, as long as the purpose of the present application can be achieved. For example, the ceramic layer and the rubber layer can be dried in an oven with a length of 5m to 15m, with the oven temperature controlled at 50°C to 80°C and the speed at 120m / min to 250m / min, to ensure the adhesion and uniformity of the ceramic layer and the rubber layer.

[0048] In the present application, during the entire coating process of step (3) and step (4), the stability of the working environment needs to be maintained, including but not limited to the control of air flow and humidity, for example, the temperature is controlled at 20°C to 30°C and the humidity is controlled at 30% to 60%.

[0049] In some embodiments of the present application, the solid content of the ceramic slurry is 20% to 50%, and the solid content of the rubber coating slurry is 5% to 20%. For example, the solid content of the ceramic slurry can be 20%, 25%, 29%, 34%, 40%, 45%, 50%, or a range consisting of any two of the values; the solid content of the rubber coating slurry can be 5%, 8%, 10%, 13%, 16%, 20%, or a range consisting of any two of the values. By controlling the solid content of the ceramic slurry and the solid content of the rubber coating slurry within the above range, the roughness of the ceramic layer and the rubber coating layer can be reduced.

[0050] In this application, D10 means the particle size value corresponding to the cumulative volume fraction of 10% after the particle population is sorted according to the particle size and the cumulative statistics are performed based on the volume of the particles. D50 means the particle size value corresponding to the cumulative volume fraction of 50% after the particle population is sorted according to the particle size and the cumulative statistics are performed based on the volume of the particles. D90 means the particle size value corresponding to the cumulative volume fraction of 90% after the particle population is sorted according to the particle size and the cumulative statistics are performed based on the volume of the particles.

[0051] Example

[0052] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0053] Test methods and equipment:

[0054] Particle size test:

[0055] The particle size of ceramic particles in the ceramic slurry and the particle size of the binder in the coating slurry were tested using a Malvern 300 particle size tester. The test conditions were: setting the shading rate to 10%, the ultrasonic time to 5 minutes, the refractive index to 1.42, the pump speed to 3000 r / min, and the absorbance to 0.1 for testing.

[0056] Select any area on the battery separator and use a scanning electron microscope (SEM) at a magnification of 10K to test the particle size of the ceramic particles and the particle size of the binder in the battery separator.

[0057] Area density test:

[0058] Cut a 100mm×100mm test sample at any position of the battery separator, then peel off the rubber layer and ceramic layer on one side of the test sample, weigh the mass of the rubber layer, recorded as m1 g, and the mass of the ceramic layer, recorded as m2 g. The surface density of the rubber layer = m1 / 0.01, the surface density of the ceramic layer = m2 / 0.01, the unit is g / m 2 .

[0059] Thickness test:

[0060] A scanning electron microscope (SEM) was used to observe the cross section of the battery separator along the thickness direction and to test the thickness of the ceramic layer and the coating layer.

[0061] Bulk density test:

[0062] Ceramic layer stacking density = ceramic layer density / ceramic layer thickness

[0063] Rubber coating layer bulk density = rubber coating layer density / rubber coating layer thickness

[0064] Surface roughness test:

[0065] The surface roughness of the ceramic layer and the coating layer was tested using the Keyence super-depth microscope VHX-X1, with a magnification of 500 times. The three-dimensional images of the ceramic layer and the coating layer were synthesized by the Keyence super-depth microscope VHX-X1 software. The surface contour line of length l was intercepted on the three-dimensional images of the ceramic layer and the coating layer respectively, and a center line was made on the surface contour line to divide the surface contour into two parts, so that the area composed of the contour line above the center line and the center line is equal to the area composed of the contour line below the center line and the center line. Where y represents the height of each point on the surface contour line relative to the midline.

[0066] Air permeability value-added test:

[0067] Cut a 100mm×100mm substrate layer or intermediate film or battery separator, and use an American Gurley 4110N air permeability tester to test it using a 100cc test gas mode. Record the time it takes for all the test gas to pass through the substrate layer or intermediate film or battery separator to obtain the substrate layer permeability or intermediate film permeability or battery separator permeability. The added value of the ceramic layer permeability = the intermediate film permeability - the substrate layer permeability, and the added value of the rubber layer permeability = the battery separator permeability - the intermediate film permeability.

[0068] Powder loss test:

[0069] Cut the battery separator into 3cm×22cm size, place it on an analytical balance and weigh it, and record the weight as M1; then fix the cut battery separator on the curved table of the friction color fastness tester (Daei Science Seiki Manufacturing Co., Ltd., RT-300S), with the glue layer facing up, clamp it and gently place the friction head, and set the number of experiments to 5 times on the operation panel of the color fastness tester. After the experiment, take out the battery separator, place it on an analytical balance and weigh it, and record the weight as M2. Then the powder loss amount M=M1-M2. If the ceramic layer is set on the two surfaces of the substrate layer, the weight of the two surfaces of the battery separator after friction test is M2, and the powder loss data is calculated based on this.

[0070] Coverage test:

[0071] The coverage of the ceramic layer and the rubber coating layer was tested using the KEYENCE super depth of field microscope VHX-X1 with a magnification of 500 times. The coverage of the ceramic layer and the rubber coating layer was automatically analyzed and calculated using the KEYENCE super depth of field microscope VHX-X1 software.

[0072] Peel strength test:

[0073] The battery separator is cut into a sample of 2.5cm long and 15mm wide, and the double-sided adhesive tape for peel strength test is pasted on the test board, and the surface part of the double-sided adhesive tape is torn off, and only the sticker with an end length of about 2cm is retained. The battery separator sample is pasted flatly to one end of the double-sided adhesive tape to tear off the surface sticker, wherein one side of the adhesive layer is in contact with the double-sided adhesive tape, and the pressure roller is rolled back and forth three times, and then the ceramic layer and the substrate layer are manually peeled off by 1cm to make the sample strip to be tested. One end of the sample strip with residual stickers is clamped in the lower chuck of a tensile machine (Jinan Sike Testing Technology Co., Ltd., TSL-1002), and the other end of the sample strip is clamped to the upper chuck to ensure that the sample strip has no tilt, and the tensile speed of the tensile machine is 50mm / min, and the load when the ceramic layer is peeled off from the substrate layer is measured, and the average value of the three results is taken as the peel strength between the ceramic layer and the substrate layer.

[0074] Bond strength test:

[0075] (1) Cut the battery separator to be tested into a sample separator of size 2.5 cm × 13 cm; cut two rectangular pieces of paper of 21 cm × 5 cm from 80 g printing paper, and fold the rectangular pieces in half along the short sides; cut out a 2.5 cm × 6 cm electrode (select the positive electrode or negative electrode according to the test requirements).

[0076] (2) Making laminated samples:

[0077] When the battery separator to be tested is a ceramic layer coated only on one surface of the substrate layer, a folded rectangular paper sheet × 1, a pole piece × 1, a battery separator × 1 and a folded rectangular paper sheet × 1 are stacked in sequence from top to bottom to make a stacked sample.

[0078] When the battery separator to be tested is a ceramic layer coated on both surfaces of the substrate layer, a folded rectangular paper piece × 1, a pole piece × 1, a battery separator × 1, a polyethylene terephthalate film (PET film) × 1 and a folded rectangular paper piece × 1 are stacked in sequence from top to bottom to make a stacked sample, wherein the specifications of the PET film used are: single-sided release 15g, 36μm×1040mm×100m.

[0079] When stacking, the adhesive layer of the battery separator to be measured for bonding strength is in contact with the electrode.

[0080] (3) A hot press machine (model: QMESYS QM940AS) is used to make the above-mentioned laminated samples into hot pressed samples; the hot pressing parameters are set as follows: temperature 70°C, pressure 0.8T, time 1S; after reaching the set temperature and the temperature is stable for 10 minutes, the above-mentioned laminated samples are placed in the hot press for hot pressing.

[0081] (4) The adhesive layer and the electrode of the hot-pressed sample are peeled off by hand to a part 5 mm away from the end, and then the tensile force is tested using a tensile testing machine (model: high-speed rail tensile testing machine AI-3000-SU); the electrode peeled off from the hot-pressed sample is fixed on the lower clamp of the tensile testing machine, and the other end not bonded to the electrode is fixed on the upper clamp of the tensile testing machine. The hot-pressed sample is clamped in the order of first clamping the lower clamp (assisted by the steel plate) and then clamping the upper clamp, keeping the sample flat, wrinkle-free, vertical and not skewed; the distance between the clamps is 65 mm, and the test speed is 300 mm / min.

[0082] There is no particular restriction on the positive electrode sheet and the negative electrode sheet used in this test method, and the electrode active material can be bonded to at least one surface of the electrode current collector by a method generally known in the art. Among the electrode active materials, non-limiting examples of positive electrode active materials include conventional positive electrode active materials that can be used for the positive electrode of a conventional electrochemical device. In particular, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide or a lithium composite oxide containing a combination thereof is preferably used. Non-limiting examples of negative electrode active materials include conventional negative electrode active materials, which can be used for the negative electrode of a conventional electrochemical device. In particular, lithium intercalation materials such as lithium metal or lithium alloys, carbon, petroleum coke, activated carbon, graphite or other carbonaceous materials are preferably used. Non-limiting examples of positive electrode current collectors include foils made of aluminum, nickel or a combination thereof. Non-limiting examples of negative electrode current collectors include foils made of copper, gold, nickel or copper alloys or a combination thereof.

[0083] Slurry solid content test:

[0084] The mass of ceramic particles used in preparing ceramic slurry is weighed using an electronic balance, recorded as G1. The mass of water used in preparing ceramic slurry is weighed using an electronic balance, recorded as G2. The solid content of ceramic slurry = G1 / (G1+G2)×100%.

[0085] The mass of the binder used in preparing the coating slurry is weighed using an electronic balance, recorded as G1', and the mass of the water used in preparing the coating slurry is weighed using an electronic balance, recorded as G2'. The solid content of the coating slurry = G1' / (G1'+G2')×100%.

[0086] Example 1-1

[0087] <Preparation of battery separator>

[0088] (1) 33 kg of alumina (Sino-Ceramic SAO-030) particles were dispersed in 67 kg of water and ground once at 500 rpm using a Langling NT-V30L horizontal sand mill with a grinding flow rate of 20 L / min. The ceramic slurry was then filtered through a 200-mesh sieve to obtain a ceramic slurry.

[0089] (2) 10 kg of polyvinylidene fluoride (Arkema LBG2400) was dispersed in 90 kg of water, ground four times at 200 rpm using a Langling NT-V30L horizontal sand mill with a grinding flow rate of 15 L / min, homogenized twice at a pressure of 400 bar using an Antos AH-PILOT 22 homogenizer with a homogenization flow rate of 10 L / min, and then filtered through a 200-mesh sieve to obtain a coating slurry.

[0090] (3) The ceramic slurry is transferred to a gravure roller through a material box. The gravure roller is in contact with the polyolefin porous substrate layer to transfer the ceramic slurry to one surface of the substrate layer. After the ceramic slurry is transferred to the substrate layer, it is dried in an oven with a length of 10 m. The oven temperature is controlled at 65° C. and the vehicle speed is 160 m / min to obtain an intermediate membrane.

[0091] (4) The above-mentioned adhesive slurry is transferred to the gravure roller through the material box, and the gravure roller is in contact with the above-mentioned intermediate film to transfer the adhesive slurry to the surface of the ceramic layer of the intermediate film. After the adhesive slurry is transferred to the ceramic layer, it is dried in an oven with a length of 10m, and the oven temperature is controlled at 65°C and the vehicle speed is 120m / min to obtain a battery separator.

[0092] During the entire coating process of step (3) and step (4), the temperature was controlled at 25° C. and the humidity was controlled at 50%.

[0093] Example 1-2

[0094] Except that the grinding speed in (1) was 300 rpm, the rest was the same as Example 1-1.

[0095] Examples 1-3

[0096] Except that the grinding speed in (1) was 700 rpm, the rest was the same as Example 1-1.

[0097] Examples 1-4

[0098] Except that grinding was not performed in (1), that is, grinding was performed 0 times, the rest was the same as Example 1-1.

[0099] Examples 1-5

[0100] Except that the grinding times in (1) were 2 times, the rest were the same as in Example 1-1.

[0101] Examples 1-6

[0102] Except that the grinding flow rate in (1) is 10 L / min, the rest is the same as Example 1-1.

[0103] Examples 1-7

[0104] Except that the grinding flow rate in (1) is 30 L / min, the rest is the same as Example 1-1.

[0105] Example 2-1

[0106] Except that the grinding speed in (2) was 100 rpm, the rest was the same as Example 1-1.

[0107] Example 2-2

[0108] Except that the grinding speed in (2) was changed to 300 rpm, the rest was the same as Example 1-1.

[0109] Example 2-3

[0110] Except that the grinding times in (2) were 2 times, the rest were the same as in Example 1-1.

[0111] Embodiment 2-4

[0112] Except that the grinding times in (2) were 6 times, the rest were the same as in Example 1-1.

[0113] Embodiment 2-5

[0114] Except that the grinding flow rate in (2) is 10 L / min, the rest is the same as Example 1-1.

[0115] Embodiment 2-6

[0116] Except that the grinding flow rate in (2) was changed to 20 L / min, the rest was the same as Example 1-1.

[0117] Example 3-1

[0118] Except that the homogenizer was used for homogenization twice at a pressure of 200 Bar in (2), the rest was the same as Example 1-1.

[0119] Example 3-2

[0120] Except for using a homogenizer at a pressure of 600 Bar for two times in (2), the rest is the same as Example 1-1.

[0121] Example 3-3

[0122] Except for using a homogenizer at a pressure of 400 Bar for one time in (2), the rest is the same as Example 1-1.

[0123] Embodiment 3-4

[0124] Except that the homogenizer was used for homogenization 3 times at a pressure of 400 Bar in (2), the rest was the same as Example 1-1.

[0125] Embodiment 3-5

[0126] Except that the homogenization flow rate in (2) is 5 L / min, the rest is the same as Example 1-1.

[0127] Embodiment 3-6

[0128] Except that the homogenization flow rate in (2) is 15 L / min, the rest is the same as Example 1-1.

[0129] Example 4-1

[0130] Except that 20 kg of alumina particles were dispersed in 80 kg of water in (1), the rest was the same as Example 1-1.

[0131] Example 4-2

[0132] Except that 40 kg of alumina particles were dispersed in 60 kg of water in (1), the rest was the same as Example 1-1.

[0133] Example 4-3

[0134] Except that 50 kg of alumina particles were dispersed in 50 kg of water in (1), the rest was the same as Example 1-1.

[0135] Example 4-4

[0136] Except that 5 kg of polyvinylidene fluoride (Arkema LBG2400) was dispersed in 95 kg of water in (2), the rest was the same as Example 1-1.

[0137] Embodiment 4-5

[0138] Except that 15 kg of polyvinylidene fluoride (Arkema LBG2400) was dispersed in 85 kg of water in (2), the rest was the same as Example 1-1.

[0139] Comparative Example 1-1

[0140] Except that homogenization is not used in (2), the rest is the same as Example 1-1.

[0141] Table 1

[0142]

[0143] Table 2

[0144]

[0145]

[0146] Table 3

[0147]

[0148]

[0149] Table 4

[0150]

[0151] In Table 1, it can be seen from the comparison of Examples 1-1 to 1-7 that by adjusting the grinding parameters of the ceramic slurry, the particle size of the ceramic slurry can be effectively adjusted, thereby affecting the surface roughness of the ceramic layer, that is, the surface roughness of the intermediate film, and then affecting the surface roughness of the rubber layer, that is, the surface roughness of the battery separator. The smaller the surface roughness of the ceramic layer, the higher the coverage of the ceramic layer, the smaller the surface roughness of the rubber layer, and the higher the coverage of the rubber layer.

[0152] By adjusting the grinding parameters of the ceramic slurry within the scope of this application, a ceramic layer with low roughness and high coverage can be obtained. The surface roughness of the ceramic layer is lower than the surface roughness of the coating layer, so that the coating slurry can be applied more evenly, effectively reducing the surface roughness of the coating layer. At the same time, by adjusting the grinding parameters and homogenization parameters of the coating slurry within the scope of this application, it is also beneficial to reduce the surface roughness of the coating layer and increase the coverage of the coating layer, thereby obtaining a battery separator with low roughness and high coverage, which can meet the stability and adhesion requirements of the battery separator during the battery production and assembly process.

[0153] In Table 2, by comparing Example 1-1 with Example 2-1 to Example 2-6, it can be seen that by adjusting the grinding parameters of the glue slurry, the particle size of the glue slurry can be effectively adjusted, and the surface roughness of the battery separator can be effectively adjusted without changing the intermediate film. The smaller the particle size of the glue slurry, the smaller the surface roughness of the glue layer, and the smaller the powder loss.

[0154] In Table 3, by comparing Example 1-1 with Example 3-1 to Example 3-6 and Comparative Example 1-1, it can be seen that the particle size of the glue slurry that has not been homogenized is significantly larger, the surface roughness of the battery diaphragm is significantly higher, and the amount of powder loss is significantly increased; by adjusting the homogenization times, pressure and homogenization flow rate, the particle size of the glue slurry can be effectively adjusted, and the surface roughness of the battery diaphragm can be effectively adjusted without changing the intermediate film.

[0155] In Table 4, by comparing Example 1-1 with Example 4-1 to Example 4-5, it can be seen that by adjusting the solid content of the ceramic slurry and the coating slurry, the slurry particle size will be affected. Under the same grinding and homogenization conditions, when the solid content increases, the slurry particle size increases, and the surface roughness of the obtained battery separator increases. When the solid content is reduced, the slurry particle size will decrease accordingly, but the coverage and surface density will be significantly reduced, and the surface roughness of the battery separator will increase. In addition, when the solid content is increased, the amount of powder loss will also increase.

[0156] According to SEM testing, the particle size of the ceramic particles of the battery separators of Examples 1-1 to 1-7, 2-1 to 2-6, 3-1 to 3-6, and 4-1 to 4-5 is all within the range of 500nm to 800nm, and the particle size of the binder of the battery separators of Examples 1-1 to 1-7, 2-1 to 2-6, 3-1 to 3-6, and 4-1 to 4-5 is all within the range of 80nm to 300nm.

[0157] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A battery separator, comprising a substrate layer, a ceramic layer disposed on at least one surface of the substrate layer, and a coating layer disposed on the surface of the ceramic layer; the ceramic layer comprises ceramic particles, and the coating layer comprises a binder; The surface roughness of the ceramic layer is 100nm-300nm; the surface roughness of the adhesive layer is 200nm-400nm; the surface roughness of the ceramic layer is less than that of the adhesive layer; the coverage of the adhesive layer is 85%-100%, and the coverage of the ceramic layer is 95%-100%.

2. The battery separator according to claim 1, wherein The thickness of the ceramic layer is 0.95 μm to 1.75 μm, and the surface density is 1.35 g / m 2 ~3.4g / m 2 , the bulk density is 0.77g / (m 2 ·μm)~2.72g / (m 2 ·μm).

3. The battery separator according to claim 1, wherein The thickness of the coating layer is 0.5 μm to 1.5 μm, and the surface density is 0.5 g / m 2 ~1.6g / m 2 , the bulk density is 0.4g / (m 2 ·μm)~1.8g / (m 2 ·μm).

4. The battery separator according to claim 1, wherein The thickness of the ceramic layer is 1.1 μm to 1.5 μm, and the surface density is 2.2 g / m 2 ~2.8g / m 2 , the bulk density is 1.47g / (m 2 ·μm)~2.55g / (m 2 ·μm).

5. The battery separator according to claim 1, wherein The thickness of the coating layer is 0.9 μm to 1.3 μm, and the surface density is 0.65 g / m 2 ~0.9g / m 2 , the bulk density is 0.5g / (m 2 ·μm)~1.0g / (m 2 ·μm).

6. The battery separator according to claim 1, wherein The ceramic particles are selected from at least one of silicon dioxide, aluminum oxide, magnesium oxide, zirconium oxide, titanium oxide, calcium oxide, boehmite, aluminum nitride, boron nitride, barium sulfate, calcium fluoride, and barium fluoride; and the particle size of the ceramic particles is 500nm to 800nm.

7. The battery separator according to claim 1, wherein The binder is selected from at least one of polyvinylidene fluoride homopolymer, polyvinylidene fluoride-trifluoroethylene copolymer, polyvinylidene fluoride-methyl methacrylate copolymer, polyvinylidene fluoride-hexafluoropropylene copolymer, polyvinylidene fluoride-acrylic acid copolymer, polymethyl methacrylate, polyethylene, and acrylate polymer; the primary particle size of the binder is 80nm to 300nm.

8. A method for preparing a battery separator according to any one of claims 1 to 7, comprising the following steps: (1) preparing a ceramic slurry: dispersing the ceramic particles in water, grinding at 300 rpm to 800 rpm for 0 to 4 times, with a grinding flow rate of 10 L / min to 30 L / min, and then filtering to obtain a ceramic slurry; (2) preparing a coating slurry: dispersing the binder in water, grinding 1 to 6 times at 100 rpm to 500 rpm, with a grinding flow rate of 10 L / min to 30 L / min, homogenizing and filtering to obtain a coating slurry, wherein the homogenization pressure is 200 bar to 600 bar, the number of homogenizations is 1 to 6 times, and the homogenization flow rate is 1 L / min to 20 L / min; (3) Ceramic layer coating: transferring the ceramic slurry to a gravure roller, the substrate layer being in contact with the gravure roller, transferring the ceramic slurry to at least one surface of the substrate layer, and drying at 50° C. to 80° C. to obtain an intermediate film; the intermediate film includes the substrate layer and the ceramic layer; (4) Glue coating: The glue slurry is transferred to a gravure roller, the intermediate film is in contact with the gravure roller, the glue slurry is transferred to the surface of the ceramic layer, and dried at 50° C. to 80° C. to obtain the battery separator.

9. The preparation method according to claim 8, wherein the solid content of the ceramic slurry is 20% to 50%, and the solid content of the coating slurry is 5% to 20%.

10. According to the preparation method of claim 8, in the ceramic slurry, the particle size of the ceramic particles satisfies: D10 ≥ 0.1 μm, 0.2 μm ≤ D50 ≤ 0.8 μm, D90 ≤ 2 μm; in the coating slurry, the particle size of the binder satisfies: D10 ≤ 1 μm, 1 μm < D50 ≤ 3 μm, D90 ≤ 6 μm.